Delivery of Dead Foetus by Episiotomy in an Indigenous Cow - Behera, Himanshu; Patra, Bijay Kumar; Das, Jayakrushna; Prasad, Uppumaguluri Venkata Sai Narayan; Naik , Madhusmita (The Indian Journal of Animal Reproduction, 2023)
The presented case of dystocia with history of protrusion of ear of foetus outside the vulva of cow was diagnosed by physical examination and successful removal of dead foetus was done per vaginally by episiotomy operation. Foetal membranes were expelled two hours after removal of dead foetus and post operative management was done by antibiotic, analgesic, vitamin B complex, dextrose saline injection and intra uterine ecbolic administration for 05 days. Animal recovered eventually and suture was removed 14 days post conduction of episiotomy operation.
Keywords: Dystocia; Episiotomy; Maternal causes